2022
DOI: 10.52628/88.1.21
|View full text |Cite
|
Sign up to set email alerts
|

The use of the internal joint stabiliser for elbow instability Report of two cases and systematic review

Abstract: The management of elbow fracture-dislocations is challenging. The internal joint stabiliser (IJS) (Skeletal Dynamics, Miami, FL) has been advocated as an alternative to traditional techniques. This article shares our initial clinical experience and provide a systematic review analysing the ability of the IJS to maintain radiographic joint reduction and the associated complication profile. Two cases of elbow fracture-dislocations treated at our centre using the IJS are presented. A systematic review of the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Case descriptions and outcomes are shown in Table 4 . The IJS is reported for the indications of chronic dislocation, 18 , 19 Ehlers–Danlos Syndrome recurrent instability, 20 acute dislocations with coronoid fracture, 21 and terrible triad variant with Essex-Lopresti injury. 22 Reports describe the use of the IJS from a medial approach 23 and a posterior approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Case descriptions and outcomes are shown in Table 4 . The IJS is reported for the indications of chronic dislocation, 18 , 19 Ehlers–Danlos Syndrome recurrent instability, 20 acute dislocations with coronoid fracture, 21 and terrible triad variant with Essex-Lopresti injury. 22 Reports describe the use of the IJS from a medial approach 23 and a posterior approach.…”
Section: Resultsmentioning
confidence: 99%
“…Schultz et al 18 reported on the IJS being used for chronic dislocation with gross instability. In a case of terrible triad injury, Jordan et al 21 reported on the IJS with removal of the device 4 months after surgery. Additionally, the same authors reported on the IJS being used in a coronoid fracture elbow dislocation case, but the device was not removed due to the patient’s choice.…”
Section: Resultsmentioning
confidence: 99%